Effect of Cigarette Smoking on High Density Lipoprotein Cholesterol Elevation - YAZAR, H.; BUYUKBAS., S. (Asian Journal of Chemistry, 2010)
The effects of cigarette smoking which is either active or passive still is in agenda by clinicians on lipid levels specifically high density lipoprotein (HDL)-cholesterol in blood. The represented study has been performed on 1006 adult persons with 598 women and 408 men between age group of 25-55 from the Cumra Government Hospital. Blood samples taken from 12 h fasting between 8 and 9.30 AM from all the patients were saved into tubes. After coagulation, HDL-cholesterol analysis was completed by separation serums. The average HDL-cholesterol levels of 1006 adult persons is found as 50.67 ± 12.30 mg/dl. HDL-cholesterol levels of men is 48.11 ± 12.59 mg/dl and for women is 52.41 ± 11.80 mg/dl. In this study, it was aimed to investigate the effect of active and passive cigarette smoking on blood HDL cholesterol levels.